The SmarterContext ontology and its application to the smart internet: A smarter commerce case study (2010)
In the smart internet interactions must be situation-aware and smart. That is, they must be realized with awareness of, and adaptation to users' individual and collective context situations. Therefore, context management is crucial to deliver contents and services that are relevant to the user's matters of concern. This paper presents the SmarterContext ontology, our semantic web approach to context representation and reasoning applicable to user-centric domains of the smart internet. We illustrate the application of the SmarterContext ontology using a personal web case study based on IBM's smarter commerce initiative. This case study demonstrates how our ontology supports context representation and reasoning to improve the relevance of retailer offers with respect to shopper situations. Our ontology is the core of the SmarterContext infrastructure, our context management solution that exploits user web interactions as sources of meaningful personal context information, and empowers users to control context gathering and provisioning. © 2013